KONVERSI ENERGI PEMOTONG KRUPUK: BERAS, TRIGU DAN IKAN SISTEM PARALEL DENGAN PUTARAN PISAU KIPAS *) - I Made Parsa (LPPM, 2010)
The aim of this action research is to mold and to cut crackers made of rice, wheat flour and fish in a quick work through the working process of a parallel system tool with the rotation of a fan knife and to give services and demonstration on how to operate the tool in producing good quality crackers in correct manner and how to carry out is maintenance. The method used in the action research supervision, demonstration and evaluation of the use of the molder (printing tool) and cutter (cutting tool) of the crackers made of rice, wheat flour and fish using a parallel system of the rotation of a fan knife. This tool has been give to Sari Rasa Food Industry in Kupang. The results of the action research are: (1) Partner Industry can become efficient in using crackers materials of rice, wheat flour and fish in producing crackers of various shapes, elastic and tough prints with the shape of circle, quadrangle or other shapes, and (2) Partner Industry my possess a crackers molder and cutter which are able to process the cracker materials of rice, wheat flour and fish which are elastic and touch to be made into various shapes of molds and flat thin cuts, where before the introduction of this tool 1 quadrangle of crackers is produced in 15 minutes, while since the operation of this tool 1 quadrangle can be produced in 3 minutes. Keywords : Crackers Molder and Cutter.